Psychosocial Issues in Patients with Chronic Hepatitis B and C - ENESCU, AURELIA (Curr Health Sci J, 2014)
Psychosocial issues and the quality of life are important components at the patients diagnosed with chronic hepatitis B and C. In function of the severity of the infection with virus B or the patients who already have cirrhosis, the treatment and psychosocial education should be improved because they have bigger problems. The frequency of psychosocial disorders seems to be raised at the patients diagnosed with chronic hepatitis B. Factors as alcohol abuse and a low social support have a negatively impact above mental health of these patients. The prevalence rate of chronic hepatitis C infection at patients with severe mental illness can be nine times higher than in healthy population. Usually patients with chronic hepatitis B have a quality of life and a mental health better than patients with chronic hepatitis C. Patients with psychiatric affections (especially institutionalized people) have generally a higher risk of being infected with virus B in comparison with general population. Patients with chronic hepatitis B and C suggest a higher grade of stigmatization from society. Despite clinical challenges which treatment with interferon at patients with chronic hepatitis and comorbidities represents, recent studies indicate the fact that treatment can be administrated in safe conditions at patients with viral chronic hepatitis and psychiatric disorders.